Educational paper: Primary antibody deficiencies - Driessen, Gertjan (Springer-Verlag, 2011)
Primary antibody deficiencies (PADs) are the most common primary immunodeficiencies and are characterized by a defect in the production of normal amounts of antigen-specific antibodies. PADs represent a heterogeneous spectrum of conditions, ranging from often asymptomatic selective IgA and IgG subclass deficiencies to the severe congenital agammaglobulinemias, in which the antibody production of all immunoglobulin isotypes is severely decreased. Apart from recurrent respiratory tract infections, PADs are associated with a wide range of other clinical complications. This review will describe the pathophysiology, diagnosis, and treatment of the different PADs.